The Use of Translation Technique in Translating the Lyrics of Owl City’s Fireflies Song from English to Indonesian - Khrisna Cahya Wibowo; Ilham Juan; Deny Kuswahono (Jurnal Sinestesia, 2023)
This study aims to analyze the translation techniques applied in translating the lyrics of Owl City’s Fireflies song from English into Indonesian by a blogspot user. The source of data of this research is the lyrics of Owl City’s Fireflies song, and method applied is qualitative descriptive approach. The results of this study in the first form are word translation techniques that have given rise to 24 data in lyrics or equivalent to 11.52% of the overall data observed. Second, the amplification technique that has been found is 9 data in lyrics or equivalent to 4.32% in the overall existing data. The third is the transposition technique where it is found as much as 1 per whole data or equivalent to 0.48%. The fourth is a reduction technique that provides data as much as 6 with a percentage of 3.84%. Finally, it is a common technique that provides data of 8 with a percentage of 2.88%. Meanwhile, the total of all data that has been analyzed is 48 or equivalent to 23.04% of the lyrics of the song Owl City’s Fireflies.